Evaluation of solid dispersions of clofazimine - Narang A.S.; Srivastava A.K. (My University, 2025)
Clofazimine (CLF) was formulated with polyethylene glycol (PEG) and polyvinyl pyrrolidone (PVP) as a solid solid dispersion (SSD) to increase the aqueous solubility and dissolution rate of the drug. Different molecular weights of PEG (1500, 4000, 6000, and 9000 Da) and PVP (14,000 and 44,000 Da) were used in different drug:carrier weight ratios (1:1, 1:5, and 1:9) and their effect on the dissolution performance of the drug was evaluated in USP Type 2 apparatus using 0.1 N HCl medium. The dissolution rate was compared with corresponding physical mixtures, a currently marketed soft gelatin capsule product, and free CLF. The effect of different methods of preparation (solvent/melt) on the dissolution rate of CLF was evaluated for PEG solid dispersions. Saturation solubility and phase solubility studies were carried out to indicate drug:carrier interactions in liquid state. Infrared (IR) spectroscopy and X-ray diffraction (XRD) were used to indicate drug:carrier interactions in solid state. Improvement in the drug dissolution rate was observed in solid dispersion formulations as compared to the physical mixtures. The dissolution rate improved with the decreasing weight fraction of the drug in the formulation. Polyvinyl pyrrolidone solid dispersion systems gave a better drug release profile as compared to the corresponding PEG solid dispersions. The effect of molecular weight of the PEG polymers did not follow a definite trend, while PVP 14,000 gave a better dissolution profile as compared to PVP 44,000. Improvement in saturation solubility of the drug in the solid dispersion systems was noted in all cases. Further, IR spectroscopy indicated drug:carrier interactions in solid state in one case and XRD indicated reduction in the crystallinity of CLF in another. It was concluded that solid-dispersion formulations of Clofazimine can be used to design a solid dosage form of the drug, which would have significant advantages over the currently marketed soft gelatin capsule dosage form.